A Novel HLA (HLA-A*0201) Transgenic Rabbit Model for Preclinical Evaluation of Human CD8(+) T Cell Epitope-Based Vaccines against Ocular Herpes - Chentoufi, Aziz A. (2010)
We introduced a novel humanized HLA-A*0201 transgenic (HLA Tg) rabbit model to assess the protective efficacy of a human CD8(+) T cell epitope-based vaccine against primary ocular herpes infection and disease. Each of the three immunodominant human CD8(+) T cell peptide epitopes from HSV-1 glycoprotein D (gD(53–61), gD(70–78), and gD(278–286)) were joined with a promiscuous human CD4(+) T cell peptide epitope (gD(49–82)) to construct three separate pairs of CD4–CD8 peptides. Each CD4–CD8 peptide pair was then covalently linked to an N(ε)-palmitoyl–lysine residue via a functional base lysine amino group to construct CD4–CD8 lipopeptides. HLA Tg rabbits were immunized s.c. with a mixture of the three CD4–CD8 HSV-1 gD lipopeptides. The HSV-gD–specific T cell responses induced by the mixture of CD4–CD8 lipopeptide vaccine and the protective efficacy against acute virus replication and ocular disease were determined. Immunization induced HSV-gD(49–82)–specific CD4(+) T cells in draining lymph node (DLN); induced HLA-restricted HSV-gD(53–61), gD(70–78), and gD(278–286)–specific CD8(+) T cells in DLN, conjunctiva, and trigeminal ganglia and reduced HSV-1 replication in tears and corneal eye disease after ocular HSV-1 challenge. In addition, the HSV-1 epitope-specific CD8(+) T cells induced in DLNs, conjunctiva, and the trigeminal ganglia were inversely proportional with corneal disease. The humanized HLA Tg rabbits appeared to be a useful preclinical animal model for investigating the immunogenicity and protective efficacy of human CD8(+) T cell epitope-based prophylactic vaccines against ocular herpes. The relevance of HLA Tg rabbits for future investigation of human CD4–CD8 epitope-based therapeutic vaccines against recurrent HSV-1 is discussed.